Drought stress alters floral volatiles and reduces floral rewards, pollinator activity, and seed set in a global plant - Rering, Caitlin C.; Franco, Jose G.; Yeater, Kathleen M.; Mallinger, Rachel E. (Ecosphere (Washington, D.C), 2020)
Plant–pollinator interactions are mediated by floral signals and by the quantity and quality of floral rewards. Biotic and abiotic disturbances can influence plant reproductive success through both direct effects on plant performance and indirect effects on pollinator attraction. In this study, we examined the effects of drought on buckwheat (Fagopyrum esculentum Moensch), a globally cultivated plant that is prone to drought stress, dependent on insect pollinators for reproduction, and increasingly utilized in on‐farm conservation. Between drought‐stressed and control plants, we compared: nectar quantity and chemical composition, pollen quantity, floral volatile emissions, visits by both managed and wild pollinators, and plant reproductive success. Drought‐stressed plants produced significantly fewer flowers and less nectar per flower, though pollen quantity per flower was unaffected. Nectar from drought‐stressed plants had a lower proportion of sucrose relative to total sugars, though overall sugar concentration was unaffected. Significantly fewer bumble bees, honey bees, and flies were recorded on drought‐stressed plants. While there was no significant difference in the quantity of total floral volatile emissions, volatile compositions differed, with drought‐stressed plants having higher emissions of (Z)‐3‐hexenol, isobutyraldehyde, 2‐methylbutanal, and 3‐methylbutanal. Finally, drought stress had negative effects on seed set and total seed mass per plant. Our results show that drought stress can have significant effects on floral traits and pollinator attraction, reducing plant reproductive success, and the nectar resources available to pollinators. Thus, the potential value of this plant in pollinator conservation and as a honey plant may be reduced under drought stress.